Early Outcomes of Routine Delayed Shunting in Carotid Endarterectomy for Asymptomatic Patients. (September 2018) - Piazza, Michele; Zavatta, Marco; Lamaina, Margherita; Taglialavoro, Jacopo; Squizzato, Francesco; Grego, Franco; Antonello, Michele
Abstract : Objective/background: The aim was to evaluate early outcomes of carotid endarterectomy (CEA) in asymptomatic patients using a standardised technique based on routine shunting after rapid plaque removal ("delayed"). Methods: A retrospective review of all asymptomatic patients who underwent CEA during a 10 year single centre experience (January 2007–December 2016) was performed. The technique was based on rapid endarterectomy with distal intimal edge visualisation, followed by routine shunt insertion; subsequent time spent on the manoeuvre and closure were completed under shunting. Primary endpoints were relevant neurological complication rate (RNCR) and death within 30 days. To better identify any difference related to changes in medical therapy, anaesthetic management, and different operators over time, patients were divided into group A (underwent CEA in the first 5 year period) and group B (underwent CEA during the second 5 year period). Univariate analysis of factors associated with RNCR was performed. Operator experience (seniority), expertise (CEA volume per year), and time period were incorporated. Results: In total, 1745 patients matched the inclusion criteria and were enrolled. Altogether, 147 (8.9%) had contemporary contralateral stenosis ≥70% and 58 (3.5%) had contralateral internal carotid artery chronic occlusion. No patient died peri-operatively; major myocardial infarction occurred in 19 patients (1.1%). Overall, peri-operative RNCR was 0.6% (major stroke: n  = 6 [0.4%]; minor stroke: n  = 4 [0.2%]). RNCR distribution was maintained equally comparing group A and B (0.8% vs. 0.4%; p  = 0.17). No differences were found in RNCR when comparing operator experience ( p  = 0.88) and expertise ( p  = 0.93). Univariable analysis found diabetes as the only clinical factor influencing RNCR (odds ratio 3.79, 95% confidence interval 1.06–13.50; p  = 0.04); none of the other factors, such as time period, operator experience, and expertise, reached statistical significance. Conclusions: Routine delayed shunting associated with standardisation of the technique seems to be a safe and effective technique and contributes to maintaining the RNCR < 1% over time and independently from operators and other clinical factors.